2010
DOI: 10.1111/j.1540-8159.2010.02723.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin Plasma Levels Predict Left Ventricular Reverse Remodeling after Cardiac Resynchronization Therapy

Abstract: Significantly higher ADM levels indicate a subgroup of patients in whom reverse remodeling can be observed after CRT. Patients with lower ADM basal values before CRT could represent a group in whom the dysfunction is so advanced that no improvement can be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…It appears to have prognostic value in patients with chronic HF [40]. Morales et al [105] showed that elevated levels of ADM at baseline were indicative of RR* after CRT. Larger studies are necessary to fully evaluate the prognostic potential of this biomarker.…”
Section: Biomarkers In Cardiac Resynchronization Therapymentioning
confidence: 99%
“…It appears to have prognostic value in patients with chronic HF [40]. Morales et al [105] showed that elevated levels of ADM at baseline were indicative of RR* after CRT. Larger studies are necessary to fully evaluate the prognostic potential of this biomarker.…”
Section: Biomarkers In Cardiac Resynchronization Therapymentioning
confidence: 99%
“…Plasma ADM concentrations were found elevated in patients with hypertension [5], renal failure [5], heart failure [6][7][8], shock [9] and diabetes mellitus [10]. ADM exhibits protective effects on heart and vasculature by inducing vasodilation and natriuresis, improving vascular endothelial function, increasing…”
Section: Introductionmentioning
confidence: 98%
“…The definition of LV reverse remodeling is highly variable in literature and changes in LV volumes or diameters have been considered by different AA [29-33]. In line with previously published papers from our group [39] we defined reverse remodelling as a >10% reduction in LVESD; low reproducibility and inaccuracy of the methods commonly used for volume calculations by 2D echocardiography are known, possibly due to the inadvertent use of foreshortened views of the left ventricle and the reliance on geometric modeling [40]. End systolic diameter measurement of is then more reliable, in particular in patients with ischemic dysfunction.…”
Section: Discussionmentioning
confidence: 56%